Analisis Faktor-Faktor yang Mempengaruhi Keputusan Perempuan Bali Untuk Bekerja di Sektor Publik di Desa Adat Kerobokan Kabupaten Badung - Ningsih, Ni Putu Devi Ekayanti; Saskara, Ida Ayu Nyoman (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 6, No. 6, Juni 2017 (pp. 920 - 1156), 2017)
Kerobokan Traditional Village is an area that has potential for tourism but also steeped in tradition. Every woman who are married will have a dual role, that is, besides working in the tourism sector is also responsible for customs and domestic activities. Every married woman in the village will be expected to indigenous people and clever in manage time well. Data collection methods used were observation, structured interviews, questionnaires. Sampling technique used are purposive sampling and snowball sampling. This study used logistic regression to see a woman's decision Bali to work. The results showed the higher the level of education and household income, then the probability increases a woman's decision to work. The higher the education, the number of dependents, cultural activities and the number of children under five, the probability of a woman's decision to work decreased.
Keywords: perempuan, bekerja, sektor publik, adat